Identification of two types of tumor necrosis factor receptors on human cell lines by monoclonal antibodies. - Brockhaus, M (1990)
The pleiotropic cyto/lymphokine tumor necrosis factor (TNF) exerts its functions by binding to specific cell-surface receptors. We have prepared two sets of monoclonal antibodies (mAbs) against TNF-binding proteins from the HL-60 (htr-mAb series) and U-937 (utr-mAb series) cell lines. The htr antibodies inhibit the binding of 125I-labeled TNF-alpha to HL-60 cells only partially, whereas they block the TNF-alpha binding to several adenocarcinoma cell lines (HEp-2, HeLa, and MCF7) almost completely. In contrast, the utr antibodies have no effect on TNF-alpha binding to the adenocarcinoma cell lines but partially inhibit TNF-alpha binding to HL-60 and U-937 cells. However, htr-9 and utr-1 antibodies in combination fully inhibit the TNF-alpha binding to HL-60 and U-937 cells. The binding of TNF-beta to HEp-2 and U-937 cells is also inhibited by htr and utr antibodies. Neither htr nor utr mAb has an effect on the TNF-sensitive murine cell lines L929 and WEHI 164. Flow cytometry studies show that mAbs htr-9 and utr-1 detect two distinct TNF-binding sites on human cell lines. Immunologic blot and immunoprecipitation analyses indicate that mAbs htr-9 and utr-1 recognize proteins of approximately 55 kDa and 75 kDa, respectively. These data provide evidence for the existence of two distinct TNF receptor molecules that contribute to varying extent to the TNF binding by different human cells.